Consultations with general practitioners on patient safety measures based on routinely collected data in primary care. - Tsang,C; Majeed,A; Aylin,P (JRSM Short Reports, 2012)
OBJECTIVES: To gauge the opinions of doctors working, or interested, in general practice on monitoring patient safety using administrative data. The findings will inform the development of routinely collected data-based patient safety indicators in general practice and elsewhere in primary care. DESIGN: Non-systematic participant recruitment, using personal contacts and colleagues' recommendations. SETTING: Face-to-face consultations at participants' places of work, between June 2010 and February 2011. PARTICIPANTS: Four general practitioners (GPs) and a final year medical student. The four clinicians had between eight to 34 years of clinical practice experience, and held non-clinical positions in addition to their clinical roles. MAIN OUTCOME MEASURES: Views on safety issues and improvement priorities, measurement methods, uses of administrative data, role of administrative data in patient safety and experiences of quality and safety initiatives. RESULTS: Medication and communication were the most commonly identified areas of patient safety concern. Perceived safety barriers included incident-reporting reluctance, inadequate medical education and low computer competency. Data access, financial constraints, policy changes and technology handicaps posed challenges to data use. Suggested safety improvements included better communication between providers and local partnerships between GPs. CONCLUSIONS: The views of GPs and other primary care staff are pivotal to decisions on the future of English primary care and the health system. Broad views of general practice safety issues were shown, with possible reasons for patient harm and quality and safety improvement obstacles. There was general consensus on areas requiring urgent attention and strategies to enhance data use for safety monitoring.